[BP.10.06] BLOOD PRESSURE RESPONSE TO CATHETER-BASED RENAL SYMPATHETIC DENERVATION IN PATIENTS WITH RESISTANT HYPERTENSION: DATA FROM THE GREEK RENAL DENERVATION REGISTRY. (September 2017) - Tsioufis, C.; Ziakas, A.; Dimitriadis, K.; Davlouros, P.; Marketou, M.; Kasiakogias, A.; Petroglou, D.; Kallikazaros, I.; Stefanadis, C.; Karvounis, C.; Alexopoulos, D.; Vardas, P.; et al.
Abstract : Objective: The efficacy of catheter-based renal sympathetic denervation (RDN) in terms of blood pressure (BP) reduction has been questioned, while "real-world" data from registries are needed. In the present study we report the complete set of 12 month data on office and ambulatory BP changes as well as the predictors for BP response to RDN from a national registry. Design and method: In 4 Greek hospital centers 79 patients with severe drug resistant hypertension (age: 59 ± 10 years, 53 males, body mass index: 33 ± 5 kg/m 2, office BP and 24-hour ambulatory BP were 176 ± 15/95 ± 13 mmHg and 155 ± 14/90 ± 12 mmHg respectively, 4.4 ± 0.9 antihypertensive drugs) underwent RDN and were followed-up for 12 months in the Greek Renal Denervation Registry. Bilateral RDN was performed using percutaneous femoral approach and standardized techniques. Results: Reduction in office systolic/diastolic BP at 6 and 12 months from baseline was -30/-12 mmHg and -29/-12 mmHg, while the reduction in 24-hour ambulatory BP was −16/−9 mmHg and −15/−9 mmHg respectively (p < 0.05 for all). Patients that were RDN responders (85%, n = 58), defined as an at least 10 mmHg decrease in office systolic BP at 12 months, compared to non-responders were younger (57 ± 9 vs 65 ± 8 years, p < 0.05), had higher baseline office systolic BP (176 ± 17 vs 160 ± 11 mmHg, p < 0.05) and 24 h systolic BP (159 ± 13 vs 149 ± 11 mmHg, p < 0.05). Stepwise logistic regression analysis revealed that age, obesity parameters and baseline office BP were independent predictors of RDN response (p < 0.05 for both), but not the type of RDN catheter or the use of aldosterone antagonists. At 12 months there were no significant changes in renal function and no new serious device or procedure related adverse events. Conclusions: In our "real-world" multicenter national registry, the efficacy of renal denervation in reducing BP as well as safety is confirmed during a 12 months follow-up. Moreover, younger age, obesity and higher levels of baseline systolic BP are independently related to better BP response to RDN.